Nationalism, internationalism, and their interplays exploring news media framing and Filipinos' reception of Facebook posts during international sporting events - Casagan, Gabriel Angelo T.; De Leon, John Solomon P.
In this study, we argue that nationalism and internationalism during international sporting events (ISEs) do not merely co-exist but interplay across both media texts and audience receptions. Upon examining Facebook posts with mixed nationalistic and internationalistic dimensions, we surfaced three interplays forming a spectrum: Conflictual (clashes serving nationalism), Paradoxical (unresolved contradictions in between), and Synergistic (harmonies benefiting internationalism). These interplays informed our analysis of 68 posts from three Philippine news outlets, revealing internal tensions between nationalism and internationalism which manifest through four interpretive lenses: Recognition, Responsibility, Legitimacy, and Impact. Reception interviews with 15 Filipinos surfaced how audiences negotiated their national and global identities, values, and aspirations—producing interplaying readings that mostly corresponded with the meanings we surfaced in frames. While nationalism remained a strong affective anchor, synergistic framings were most widely accepted, suggesting their promise as diplomatic framing strategies. We argue that Comprehension, or the audience’s understanding of texts, serves as the hinge between message framing and audience reception. By giving analytical primacy to Comprehension and how it interacts with other aspects of reception, we better understand how personal experiences influence the way people make sense of local content during diplomacy-driven events like ISEs.